The Musical Identity of the Roma People on the Streets of Belgrade - АКСИЋ, НИНА (Bulletin of the Institute of Ethnography SASA, 2023)
This paper deals with the musical street practice of the Roma people on the territory of Belgrade. An attempt shall be made to present this practice in its entirety, with all its particularities, based on data obtained in the field (through interviews with performers), Internet sources (YouTube videos, texts, etc.), and academic literature. The Romani practice is possibly the most common street musical practice on the territory of Belgrade, and while it is undoubtedly diverse, it still possesses numerous characteristics which shape its particular identity. Therefore, the elements of the aforementioned musical practice shall be presented and analyzed, including: 1. forms of musical performance, 2. Types  of performing ensembles, 3. choice and condition of the instruments used in performing, 4. choice of musical repertoire, 5. the language being sung in, 6. choice of public spaces at which it takes place, 7. events and special occasions during which this musical practice occurs, 8. career development and 9. Child exploitation. The aim of the paper is to provide a relevant insight into the special musical identity of the Romani street musical practice in Belgrade by way of analyzing the segments of this street musical practice presented. Moreover, the goal of this research is to construct a model which may serve to conduct further research into the Romani street musical practice in other Serbian cities, as well as enable a comparative analysis and insight into the common, general features of this musical identity.
Keywords: musical identity; street musical practice; Romani music; Belgrade; Roma people